2016
DOI: 10.1186/s12912-016-0134-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of social support and socio-demographic characteristics with poor self-rated health and depressive symptomatology among single mothers in Cyprus: a descriptive cross-sectional study

Abstract: BackgroundThe number of single-parent families headed by mothers is rapidly growing worldwide. A large part of the international literature reveals that single motherhood is associated with increased levels of chronic stress, mainly due to economic distress and reduced levels of social support, which may eventually lead to physical and psychological illness. Most published research comes from Northern Europe and the US, while it is accepted that both social welfare systems and societal factors vary substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 55 publications
0
45
1
1
Order By: Relevance
“…Furthermore, between full-time employees, due to them being unable to take up other activities, they have experienced lower social support and higher stress ( 71 ). Although, Elena ( 72 ) and Boen ( 73 ) reported association between the income with social support and stress, Nazari’s findings indicate no relation between the two variables ( 74 ). In a research on patients suffering from cancer and hemodialysis, it has been mentioned that the perceived social support in people who are in a more favorable economic situation is better than those with poor or average economic state ( 75 ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, between full-time employees, due to them being unable to take up other activities, they have experienced lower social support and higher stress ( 71 ). Although, Elena ( 72 ) and Boen ( 73 ) reported association between the income with social support and stress, Nazari’s findings indicate no relation between the two variables ( 74 ). In a research on patients suffering from cancer and hemodialysis, it has been mentioned that the perceived social support in people who are in a more favorable economic situation is better than those with poor or average economic state ( 75 ).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have focused specifically on the mental health of women. One study found that single mothers exhibited depression levels that are three times that of the general population, related to factors like financial constraints and single-motherhood status [ 87 ]. Another study assessed female Greek-Cypriot university students, reporting an association between disordered eating and many psychological variables including higher levels of anxiety about weight and internalisation of thin body ideals, findings that are consistent with other populations living in warmer climates [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family kin networks have been identified as important determinants of mental well-being. In particular, single motherhood is related to poor mental health [14]. Single mothers demonstrate higher levels of psychiatric symptomatology, e.g.…”
Section: Introductionmentioning
confidence: 99%